A study on compatibility of experimental effective atomic numbers with those predicted by ZXCOM - Eyecioglu, Onder; El-Khayatt, A. M.; Karabul, Yasar; Icelli, Orhan (SPRINGER SINGAPORE PTE LTD, 2017)
In this study, effective atomic numbers (Z(eff)) of materials determined at different experimental conditions by measuring the elastic-to-inelastic gamma-ray scattering ratios are compared to ZXCOM predictions. It also presents the experimental data obtained via the transmission technique. The agreement and disagreement between ZXCOM and experimental values are investigated. The theoretical basics of determining Z(eff) by scattering mode are outlined. The study shows that choosing appropriate experimental conditions can provide a good compatibility between the experimental results and theoretical ZXCOM calculations.
Keywords: Effective atomic number; ZXCOM; Rayleigh scattering; Compton scattering; COMPTON-SCATTERING; ENERGY-ABSORPTION; INELASTIC-SCATTERING; CROSS-SECTION; COHERENT; COEFFICIENTS; RAYLEIGH; GLASSES; SAMPLES; RATIO; Nuclear Science & Technology; Physics